2009
DOI: 10.1111/j.1365-2982.2009.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Are pediatric and adult‐onset cyclic vomiting syndrome (CVS) biologically different conditions? Relationship of adult‐onset CVS with the migraine and pediatric CVS‐associated common mtDNA polymorphisms 16519T and 3010A

Abstract: Pediatric cyclic vomiting syndrome (CVS) is associated with a high prevalence of co-morbid migraine and other functional disorders, and with two adult migraine-associated mitochondrial DNA (mtDNA) polymorphisms: 16519T and 3010A. These potential associations have not been studied in adult CVS. The objective of this study is to determine the prevalence of 16519T and 3010A mtDNA polymorphisms and other functional disorders in adult CVS patients. Adults with CVS recruited from the University of Kansas meeting Rom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 17 publications
1
39
1
1
Order By: Relevance
“…Patients with CVS often have numerous emergency admissions for many years before a diagnosis is made, typically about 5 years. It has been suggested that adult-onset CVS is a syndrome different from childhood-onset CVS, being more severe [7,19]. However, in this cohort, childhood-onset CVS appeared to be more severe, with an average of 25 attacks per year compared with 10 in adults.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Patients with CVS often have numerous emergency admissions for many years before a diagnosis is made, typically about 5 years. It has been suggested that adult-onset CVS is a syndrome different from childhood-onset CVS, being more severe [7,19]. However, in this cohort, childhood-onset CVS appeared to be more severe, with an average of 25 attacks per year compared with 10 in adults.…”
Section: Discussioncontrasting
confidence: 61%
“…The cause is likely a result of disorders of the central neural pathways and neuroendocrine mediators involved in the brain-gut pathways of nausea and vomiting [3]. There is also some evidence to suggest underlying abnormalities in the mitochondria [5][6][7] and the autonomic nervous system [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Persons with mitochondrial defects may be predisposed to the onset of vomiting during periods of increased energy demands, such as infection and stress 36. Studies of mitochondrial DNA polymorphisms have described an association of 16519T and 3010A polymorphism with paediatric CVS and adult migraines 37 38. However, no association was demonstrated in adult-onset CVS,37 39 suggesting that the two are genetically distinct.…”
Section: Aetiology and Pathophysiologymentioning
confidence: 99%
“…Some studies have noted striking similarities in many characteristics across the age groups [20], but other studies have noted that adult CVS differs by having more features of abdominal pain, longer duration [21] and a difference in the prevalence of mitochondrial polymorphisms (e.g. 16519C-T and 3010G-A) [22].…”
Section: Introductionmentioning
confidence: 98%